Advanced Bistatic and Multistatic SAR Concepts and Applications - Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2006)
Tutorial on Bistatic and Multistatic Synthetic Aperture Radar from EUSAR 2006 Conference
DLR Import::2019-04-03